Pengaruh Kepemimpinan dalam Peningkatan Motivasi Kerja PNS di Kantor Kecamatan - Zaenal Akhmad; Hasran Hasran; Rahman Rahman (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2022)
Abstract This study aims to determine the influence of sub-district leadership on increasing the work motivation of civil servants in Bontomatene District, Selayar Regency. This research was conducted in the area of ​​the Bontomatene District Office, Selayar Regency. In this study the authors used a survey research basis. While the type of research used was to obtain research data, the population used by the author was all employees of the Bontomatene District office, Selayar Regency, while the informants were the Bontomatene Sub-District Head and the Bontomatene Sub-District Secretary. The sampling technique in this study is the purposive sample method. To collect the required data the author collects data through: Library research, field research, interviews, questionnaires and online data tracking. The collected data will be analyzed using a qualitative approach. The results of the research show that the leadership of the sub-district head which influences employee motivation seen from planning is quite good. This can be seen with an average score of 2.2 which shows that the planning carried out by the Bontomatene Sub-District Head is in the moderate category. All employees have been involved in planning the sub-district work program, but the resulting score is still in the moderate category. Therefore, employee involvement still needs to be improved. In addition to planning indicators, researchers also use indicators of effective communication. The communication carried out by the Bontomatene sub-district head to his subordinates still needs to be improved.